Assessing Public-Sector Readiness for Artificial Intelligence in Egypt - Anwar, Renad Ahmed (AUC Knowledge Fountain, 2026)
Artificial intelligence (AI) is increasingly adopted in public-sector contexts, yet successful implementation depends on organizational readiness, particularly in developing countries. This study assesses the readiness of Egypt’s public sector for AI adoption using a qualitative expert opinion methodology. Semi-structured interviews were conducted with senior professionals from global technology firms with extensive experience working with public-sector entities in Egypt. Guided by by an integrated framework combining organizational readiness theory, the Technology–Organization–Environment (TOE) framework, and public value and governance perspectives, the study examines strategic, organizational, human, technological, societal, and governance dimensions of AI readiness. The findings indicate that while Egypt demonstrates strong national ambition and early strategic commitment to AI, significant readiness gaps persist at the organizational and operational levels. These include limited internal capabilities, skills shortages, data and infrastructure challenges, and evolving governance and regulatory frameworks. The study contributes empirical insights to the limited literature on public-sector AI readiness in developing-country contexts and offers policy-relevant recommendations to support effective, sustainable, and responsible AI adoption in Egypt’s public sector.